Determination of antioxidant activity in methanolic and chloroformic extracts of Momordica charantia - Rezaeizadeh, Alireza; Abu Bakar @ Zakaria, Md Zuki; Abdollahi, Maryam; Goh, Yong Meng; Mohamed Mustapha, Noordin; Hamid, Muhajir; Tengku Ibrahim, Tengku Azmi (Academic Journals, 2011)
The aim of this study was to determine and compare the antioxidant activity of methanolic and chloroformic extracts of Momordica charantia (MC) fruit. In this study, the total antioxidant and free radical scavenging activities in methanolic and chloroformic were measured by ferric thiocyanate (FTC), thiobarbituric acid (TBA) and 1, 1-diphenyl-2-picryl-hydrazyl (DPPH) methods. Total phenol and flavonoid contents of the MC extracts were also evaluated. The total antioxidant activity results indicated that, the inhibition percent of methanolic extract was significantly higher than the inhibition percent of chloroformic extract in the FTC and TBA methods. A higher IC50 value for free radical scavenging was found for methanolic extract when compared with chloroformic extract. Methanolic extract contained a significantly higher concentration of total phenols and flavonoids when compared with chloroformic extract. Methanolic extract contained more potent antioxidant and high polyphenol compounds when compared with chloroformic extract. The present study, confirmed that, the type of solvent has an important role in detecting plant compounds. The natural plant antioxidants and phenolics compounds in MC have the capability of being used in food systems to preserve food quality.